Use of seashell as cement replacement in construction material: A review - Sofia Adibah, Jasni; Khairunisa, Muthusamy; Hanis Nadiah, Ruslan; Hamada, Hussein; Ezahtul Shahreen, Ab Wahab (Penerbit UMP, 2024)
Growing construction industry boost cement manufacturing industry which consume a large amount of natural resources and releases greenhouse gases during cement production affects the environment. A lot of researchers attempt to find alternatives in integrating waste into concrete mixes and can be reused in cementitious construction material. Seashells are one of the waste materials that would give harm to their own biodiversity as it would occupy the landfills and seashores. Seashell is known to be very hard and protective on the outer layer produced by an animal that lives in the sea. This review paper is focused in using seashells as cement replacements in construction material. This academic review paper examines the potential of utilizing seashells, including various types such as a cockle, clam, oyster, and scallop as a sustainable and environmentally beneficial alternative to traditional usage in construction. By exploring the practical applications and economic viability of seashell-based concrete, this research aims to contribute to the broader discourse on eco-friendly construction practices and sustainable resources utilization in the construction industry.